2015
DOI: 10.1186/s12915-015-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage branching as a strategy for proliferative control

Abstract: BackgroundHow tissue and organ sizes are specified is one of the great unsolved mysteries in biology. Experiments and mathematical modeling implicate feedback control of cell lineage progression, but a broad understanding of what lineage feedback accomplishes is lacking.ResultsBy exploring the possible effects of various biologically relevant disturbances on the dynamic and steady state behaviors of stem cell lineages, we find that the simplest and most frequently studied form of lineage feedback - which we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 53 publications
0
57
0
Order By: Relevance
“…The molecule y increases the differentiation rate of the stem cells and thus limits their expansion rate. This type of feedback has been demonstrated for many tissues, such as blood, skin, skeletal muscle, olfactory epithelium, bone, hair, and more (Lander et al, 2009;Buzi et al, 2015). In many of these tissues, the secreted molecule belongs to the TGF-b family (Lander et al, 2009).…”
Section: Evolutionary Stable Strategies In Tissues With Stem Cellsmentioning
confidence: 97%
“…The molecule y increases the differentiation rate of the stem cells and thus limits their expansion rate. This type of feedback has been demonstrated for many tissues, such as blood, skin, skeletal muscle, olfactory epithelium, bone, hair, and more (Lander et al, 2009;Buzi et al, 2015). In many of these tissues, the secreted molecule belongs to the TGF-b family (Lander et al, 2009).…”
Section: Evolutionary Stable Strategies In Tissues With Stem Cellsmentioning
confidence: 97%
“…In other tissues, members of the TGF-b gene family, which have known roles in cell differentiation [98] and brain development [99], function as the signal molecule. TGF-b signals are only effective across small spatial scales suggesting local feedback operates at a tissue-specific rather than whole organ level [96]. It is an intriguing hypothesis that modification of such signals would allow local control and variation in cell proliferation, facilitating mosaic evolution.…”
Section: (E) Developmental Models Of Mosaic Evolutionmentioning
confidence: 99%
“…For example, mechanisms of local control of proliferation may be necessary to produce mosaic patterns of evolution. Recently, Buzi et al [96] demonstrated the potential for descendent cells to regulate the duration of proliferative division in their own progenitor pools through 'integral feedback' mediated by secreted molecules. Under this model, the strength of an inhibitive signal on cell division increases as descendent cells accumulate until it causes a cessation of proliferation.…”
Section: (E) Developmental Models Of Mosaic Evolutionmentioning
confidence: 99%
“…1B. Closely related control mechanisms have also been considered in [34 ] in the context of fold-change detection and in [35 ] in the context of stem cell differentiation even though, in the latter case, the model is considered at a cellular level rather than at a molecular level.…”
Section: Resultsmentioning
confidence: 98%